Biosynthesis of Iron Oxide Nanoparticles Using Food Origin Citrobacter freundii in Optimized Conditions - Marwa H. AlKhafaji; Raghdan H. Mohsin; Mokhtar Jawad Kadhim (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
Sustainability, Ecofriendly, and green technology are key principles guiding the biosynthesis of nanoparticles in this research.  This work aimed to utilize Iron oxide nanoparticles (IONPs) as antimicrobial agents, what offers a promising solution to combat antibiotic-resistant pathogens. In this study, 120 food samples were analyzed. Food origin Citrobacter freundii was isolated and identified accurately to be used then for the biosynthesis of Iron oxide nanoparticles. Iron Oxide Nanoparticles were synthesized and characterized using different assays. Atomic force microscope was the principle characterization technique. Their antimicrobial activity was tested against foodborne and clinical bacterial isolates. The results of this study revealed that the biosynthesized IONPs were in a diameter of 32.86 nm with magnetic properties. The biosynthesized IONPs inhibited the biofilm formation of both food and clinical isolates. The main conclusion of this work is that food origin C. freundii is an excellent reducing agent in the biosynthesis of these bioactive nano-scale materials. This research is the first to synthesize Ferric oxide NPs using C. freundii marking a new approach in the field.  Clinical C. freundii required a higher IO-NPs dose more than foodborne isolates. This calls for stronger therapies, while foodborne C. freundii still poses contamination risks despite lower resistance. Addressing both could improve antimicrobial treatments and food safety.